Vector-borne and zoonotic infections and their relationships with regional and socioeconomic statuses: An ID-IRI survey in 24 countries of Europe, Africa and Asia - Saydam, Fatma Nurhayat; Erdem, Hakan; Ankarali, Handan; Ramadan, Manar Ezz El-Arab; El-Sayed, Nagwa Mostafa; Civljak, Rok; Rodriguez-Morales, Alfonso J. (Elsevier Sci Ltd, 2021)
Background: In this cross-sectional, international study, we aimed to analyze vector-borne and zoonotic infections (VBZI), which are significant global threats. Method: VBZIs' data between May 20-28, 2018 was collected. The 24 Participatingcountries were classified as lower-middle, upper-middle, and high-income. Results: 382 patients were included. 175(45.8%) were hospitalized, most commonly in Croatia, Egypt, and Romania(P = 0.001). There was a significant difference between distributions of VBZIs according to geographical regions(P < 0.001). Amebiasis, Ancylostomiasis, Blastocystosis, Cryptosporidiosis, Giardiasis, Toxoplasmosis were significantly more common in the Middle-East while Bartonellosis, Borreliosis, Cat Scratch Disease, Hantavirus syndrome, Rickettsiosis, Campylobacteriosis, Salmonellosis in Central/East/South-East Europe; Brucellosis and Echinococcosis in Central/West Asia; Campylobacteriosis, Chikungunya, Tick-borne encephalitis, Visceral Leishmaniasis, Salmonellosis, Toxoplasmosis in the North-Mediterranean; CCHF, Cutaneous Leishmaniasis, Dengue, Malaria, Taeniasis, Salmonellosis in Indian Subcontinent; Lassa Fever in West Africa. There were significant regional differences for viral hemorrhagic fevers(P < 0.001) and tick-borne infections(P < 0.001), and according to economic status for VBZIs(P < 0.001). The prevalences of VBZIs were significantly higher in lower-middle income countries(P = 0.001). The most similar regions were the Indian Subcontinent and the Middle-East, the Indian Subcontinent and the North-Mediterranean, and the Middle-East and North Mediterranean regions. Conclusions: Regional and socioeconomic heterogeneity still exists for VBZIs. Control and eradication of VBZIs require evidence-based surveillance data, and multidisciplinary efforts.
Keywords: Zoonosis; Economic status; Tick; Vector; Infection